O zooplâncton da laguna hipersalina de Araruama (RJ) com ênfase na biologia de Oithona oswaldocruzi Oliveira, 1945 (Cyclopoida, Copepoda) - Rodrigues, Claudia Leal (1998)
The Araruama Lagoon, located in the state of Rio de Janeiro, measuring 220 Km2, has a great ecological and socio-economic importance. It is the largest permanent hypersaline lagoon in the world. Its constant hypersalinity can be explained by its narrow communication with the ocean, its shallowness, and the climate conditions. The increasing anthropic influence is one of its main problems. ln order to analyze the zooplankton composition and its spatial and temporal variations during one annual cycle, the samples were taken every 16 days, during 1994, in 10 stations in the lagoon. Simultaneously, temperature, salinity and transparency of water were measured. The daily variation of the zooplankton was analyzed by drags in diff erent hours of the day in two periods, from November 7 fh to 9 lh 1993, and April 7 fh to 10th 1995. The results revealed the predominance of a zooplankton of small size and low diversity, composed basically of the eurihaline specie of copepod called Oithona oswa/docruzi and bivalve larvae. The other holoplanktonics organisms ·rarely found, may not reproduce in the lagoon. The O.oswa/docruzi is able to complete its life cycle, suggesting that it is adapted to the stressing conditions of the environment. The greatest abundance of copepods and bivalve larvae happens from September to November. The percentage of females is always greater than the percentage of males. Near the reproduction periods, though, the percentage of males increases. The temperature seems to be the main factor of influence in reproduction. The high proportion of copepodits, compared to that of the adults may be related to intraspecific competition. Meteorological factors seem to influence in spatial and daily variation of the organisms, that tend to be more abundant in the stations located near the entrance of the lagoon.